Neutropenic enterocolitis caused by antithyroid drug - case report - Nina Kobilica; Marjan Skalicky; Andrej Bergauer; Vojko Flis (Acta Medico-Biotechnica, 2021)
Purpose: Neutropenic enterocolitis (NE) is rarely reported condition, characterized by necrotizing enterocolitis. It is unusual acute complication of neutropenia. Although it was most often associated with leukemia or cancer patients it can be caused by any drug or poison associated with neutropenia. We present a case of neutropenic enterocolitis in a patient who received antithyroid drug propylthiouracil. To the best of our knowledge, this is the first description of NE associated with antithyroid drug propylthiouracil and extensive necrosis of small bowel.Case report: A 50- year-old woman with no significant past medical history presented to the emergency department of a community hospital complaining of intractable abdominal pain, nausea, vomiting and diarrhea. The onset of symptoms was acute. Physical examination of abdomen was unremarkable. Ultrasound examination revealed free liquid in abdominal cavity. Severe neutropenia with elevated CRP was present. Toxicology was negative. As patient was becoming more and more confused and pain could not be controlled by morphine immediate surgery was performed. Surgical exploration of abdomen revealed gangrenous ascendent colon and terminal ileum. Diseased bowel parts were resected. After surgery patient was transferred to intensive care unit. She was discharged from hospital after several month of intensive medical treatment and repeated surgical procedures. Upon later questioning she noticed that three months before emergency admission to hospital she started with antithyroid drug (propylthiouracil).Conclusion: Physicians should be aware that antithyroid drugs can be associated with agranulocytosis and NE. Neutropenic patients, presenting with either generalized or focal abdominal pain, along with a fever, should uniformly be considered at a risk for NE.